Detection and identification of cacao black pod causal agent by polymerase chain reaction (PCR) - Alsultan, Wael M. K.; Vadamalai, Ganesan; Ahmad, Khairulmazmi; Rashid, Osamah (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
Among the Phytophthora species that cause black pod of cacao, P. palmivora is the most virulent, posing a serious threat to cacao production in Asia. Correct identification of the species causing the black pod and understanding the virulence factors involved are important for developing sustainable disease management strategies. The present study had revealed molecular characterization of thirty isolates of P. palmivora randomly obtained from infected cocoa pods in different states in Malaysia. All 30 isolates of P. palmivora were subjected to molecular identification methods using ITS rDNA, the mitochondrial cox1 and elongation factor 1α genes. Phylogenetic tree for P. palmivora was constructed using the sequencing of ITS rDNA, mitochondrial cox1 and elongation factor 1α genes. Different Phytophthora spp. sequencing had been chosen from NCBI and Pythium undulatum as outgroup. Molecular identification of rDNA confirmed that all isolates were Phytophthora palmivora. Phylogenetic analysis based on rDNA sequencing of different genes were separated different species of Phytophthora to various clades. P. megakarya is considered the closest species with P. palmivora based on ITS rDNA, translation elongation factor 1alpha and Cox subunit I. The significant of these findings are also viewed in terms of the increasing importance of Phytophthora diseases in this region.